Mostly sunny : how I learned to keep smiling through the rainiest days - Dean, Janice, 1970- (Harper, an imprint of HarperCollinsPublishers, 2019)
The "Fox & Friends" meteorologist discusses her marriage to a 9/11 firefighter, her battle with multiple sclerosis, and the impact of sexism on her career, revealing the strength of deliberate optimism in the face of any challenge.